Perancangan Sistem Pakar Dalam Diagnosa Penyakit Varicella pada Anak dengan Metode Certainty Factor Berbasis Web - Abdul Rahman Anshar; Raja Ayu Mahessya; Devia Kartika (Majalah Ilmiah UPI YPTK, 2019)
Varicella is a disease that easily attacks children and adults or pregnant women. Varicella is a symptom of a disease caused by a virus in food and the environment that can be indicated as a disease that will be suffered by a child. Varicella can spread easily from an infected person to anyone who has not been exposed to chickenpox before and has not received a chickenpox vaccine. In Indonesia, varicella disease is of less concern to the public due to the community's assumption that varicella will heal itself. Therefore an expert system was designed to determine the classification of varicella disease in children. The method used in expert systems is Certainty Factor. The Certainty Factor method uses certainty to strengthen the results of decisions from the expert system. Expert system can provide solutions and ways of handling varicella disease in children with the diagnosis process carried out efficiently and saves time in helping the community or parents in prevention that occurs. This web-based expert system application is built with the PHP programming language and MySQL data storage.